Unplanned blood use within 24 hours of emergency department presentation: A cohort study in an ageing population. (26th September 2021) - Simon, Geoff I; Craswell, Alison; Thom, Ogilvie; Fung, Yoke Lin
Abstract: Objective: This research aims to elucidate drivers of blood use in an older population, with a focus on unplanned transfusions following ED presentation. Methods: In a retrospective cohort study we examined 2015 data for ED presentations and blood use in two hospitals serving a population containing a high proportion (21%) of adults aged ≥65 years. Unplanned blood use was defined as any transfusion ≤24 h of presentation. Data were analysed by age, sex, Major Diagnostic Category, triage category and time to transfusion. Results: A total of 5294 blood components were transfused, comprising red cells ( n  = 3784), fresh frozen plasma ( n  = 657), platelets ( n  = 563) and cryoprecipitate ( n  = 290). Men aged ≥65 years were the highest users (40%, 2107 components). Unplanned transfusions accounted for 28% ( n  = 1057) of annual red cell use. Of 85 014 ED presentations, 494 (0.6%) were associated with unplanned red cell transfusion. Four Major Diagnostic Categories accounted for 81% ( n  = 853) of unplanned red cell use: gastrointestinal ( n  = 375), haematology ( n  = 267), trauma ( n  = 144) and cardiovascular ( n  = 67). Over one‐fifth of unplanned transfusions (21%, n  = 222 of 1057) were associated with ICD‐10 codes for anaemia as a reason for presentation within the Haematology Major Diagnostic Category. Adults aged ≥65 years accounted for 62% of overall red cell use and 61% of transfusions ≤24 h of presentation. Odds of unplanned red cell transfusion increased with age, peaking at odds ratio 28.5 (95% confidence interval 14.2–57.4) in those aged 85 years and above. Conclusions: Unplanned blood use accounted for 28% of annual hospital blood consumption. Blood component use increased with age and was greatest in older men. A significant burden of anaemia treatment was identified by the ED. Abstract : Unplanned blood use accounted for 28% of annual hospital blood consumption. Blood component use increased with age and was greatest in older men. A significant burden of anaemia treatment was identified by the ED.